2005
DOI: 10.2105/ajph.2004.054494
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Built Environment in the Disablement Process

Abstract: The Disablement Process model explicates the transition from health conditions to disability and specifically emphasizes the role of intervening factors that speed up or slow down the pathway between pathology and disability. We used hierarchical Poisson regression analyses with data on older adults from central North Carolina to examine the role of the built environment as a modifying factor in the pathway between lower extremity functional limitations and activities of daily living. We found that, despite de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 25 publications
8
164
1
1
Order By: Relevance
“…For men, we found that a scale reflecting street connectivity and age of homes in the tract was associated with reduced risk of limitations in IADLs -activities conducted primarily in the home such as cooking as well as activities that my involve going out into the community such as shopping. Such findings are similar to Clarke & George (2005), who found among older adults in central North Carolina greater independence in IADLs among those living in areas of greater land use diversity. When we probed this finding using two waves of data, we found that increases in IADL limitations were larger among those who moved and that those who moved generally relocated to places with lower connectivity scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For men, we found that a scale reflecting street connectivity and age of homes in the tract was associated with reduced risk of limitations in IADLs -activities conducted primarily in the home such as cooking as well as activities that my involve going out into the community such as shopping. Such findings are similar to Clarke & George (2005), who found among older adults in central North Carolina greater independence in IADLs among those living in areas of greater land use diversity. When we probed this finding using two waves of data, we found that increases in IADL limitations were larger among those who moved and that those who moved generally relocated to places with lower connectivity scores.…”
Section: Discussionsupporting
confidence: 90%
“…They found that functional loss was related to self-reported problems with neighborhoods, including excessive noise, inadequate lighting at night, heavy traffic, and limited public transportation. Clarke and George (2005) examined the role of the built environment in the disablement process for 4,154 adults ages 65 and older from central North Carolina. Using survey responses linked to 1990 census tract data, they found that older adults reported greater independence in instrumental activities of daily living (e.g., shopping, managing money, household chores) when they lived in environments with more land use diversity and that among those with functional limitations housing density was inversely related to self-care disability.…”
Section: Introductionmentioning
confidence: 99%
“…Sprawl's impact on people with disabilities has been discussed in general terms, and has been the subject of little empirical assessment (for a recent exception examining the impact of sprawl on the elderly, see Clarke and George [2005]). The impact that sprawl can have on people with mental illness struggling to integrate into the community has yet to be explicitly discussed in the literature.…”
Section: The Trend Toward Increasing Sprawl In Congregate Housingmentioning
confidence: 99%
“…This was associated with many outcomes in cross-sectional research, even after adjustment for individual characteristics, including depression, [51][52][53] 67 and disability. [68][69][70][71] Other studies failed to find an association. [72][73][74] A causative role for neighbourhood disadvantage in these associations is supported by a number of longitudinal studies, which have found similar effects after accounting for individual level characteristics.…”
Section: Summary Of Epidemiologic Evidencementioning
confidence: 99%